2013
DOI: 10.4062/biomolther.2013.085
|View full text |Cite
|
Sign up to set email alerts
|

Nucleic Acid Aptamers: New Methods for Selection, Stabilization, and Application in Biomedical Science

Abstract: The adoption of oligonucleotide aptamer is well on the rise, serving an ever increasing demand for versatility in biomedical field. Through the SELEX (Systematic Evolution of Ligands by EXponential enrichment), aptamer that can bind to specific target with high affinity and specificity can be obtained. Aptamers are single-stranded nucleic acid molecules that can fold into complex threedimensional structures, forming binding pockets and clefts for the specific recognition and tight binding of any given molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
126
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(129 citation statements)
references
References 115 publications
0
126
0
3
Order By: Relevance
“…Aptamers with high affinity and specificity have been developed to target peptides, proteins, drugs, organic and inorganic molecules and even whole cells (7)(8)(9). Accumulating evidence has indicated that certain aptamers showed great therapeutic efficacy both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aptamers with high affinity and specificity have been developed to target peptides, proteins, drugs, organic and inorganic molecules and even whole cells (7)(8)(9). Accumulating evidence has indicated that certain aptamers showed great therapeutic efficacy both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Using the systematic evolution of ligands by exponential enrichment (SELEX) technique, several aptamers with high affinity and specificity for target proteins were previously selected from a library of randomized sequences in vitro, including single-stranded DNA (ssDNA) or RNA oligonucleotides (7)(8)(9). For instance, Bell et al (10) developed an oligonucleotide designated as NX1838 (2'-fluoropyrimidine, RNA-based oligonucleotide/40-kDa-PEG) that inhibited vascular endothelial growth factor 165 (VEGF165)-mediated cell response in vitro by directly targeting the VEGF165 factor.…”
Section: Introductionmentioning
confidence: 99%
“…However, therapeutic aptamers alone are not sufficiently stable for in vivo delivery, so they are usually modified or conjugated to vehicles that are resistant to nucleases to improve their residence time (33). Considering that PEGylation is one of the most commonly used modifications of aptamers (34,35), we analyzed the therapeutic effects of PEGylated A11 in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…In this process, a synthesized mirror image form (eg, d-polypeptide) of the target molecule (eg, l-polypeptide) is used as the target to screen aptamers by in vitro selection from a synthetic natural d-oligonucleotide library at first. Then, the selected d-aptamers are synthesized as Spiegelmers (l-aptamers), which can bind to the original target molecules (eg, l-polypeptide) using enantiomeric l-ribonucleotides [16]. Vater et al reported a mixed 39-mer antiglucagon DNA/RNA-Spiegelmer modified with 2¢-oxygens on the sugar backbone and conjugated them with PEG at the 5¢-end (NOX-G15; Noxxon Pharma).…”
Section: Aptamers For Dmmentioning
confidence: 99%